Spatial Justice Of having the advantages Of Facilities And Service In Rural Settlements Villages Of Province Gilan) - majid yasoori; sideh fatemeh emami; Maryam sejodi (تحقیقات کاربردی علوم جغرافیایی, 2016)
The above research evaluates the access and use of rural services of the villages in the province of Gilan, as examples of reducing inequalities and increasing the development. The method used in this article is applicable in terms of target, and cross-sectional in tems of identity. To do this research, morris model, indexing method, standardization and dividing by average are used. After comparing the villages of the province in terms of rural services, the obtained outcome indicates that accomplished results and ranking are in high agreement, so that in all models, villages of Saravan, Kelishami and Gol Sefid have the most access to facilities and services and mountain villages of Talesh, Shuil and Eshkevar Olia are the most deprived villages in rural facilities and services, respectively. Based on studied indicators, the distance between deprived and wealthy villages flactuates from 2 to 10 times. This situation reflects the gross spatial inequality of having advantage of facilities and services in the villages of province Gilan.